2000
DOI: 10.1104/pp.123.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Targeting of a Fibrillarin Homolog from Arabidopsis

Abstract: Fibrillarin is a nucleolar protein known to be involved in the processing of ribosomal RNA precursors. We isolated AtFbr1, a cDNA encoding a homolog of fibrillarin in Arabidopsis. The cDNA is 1.2 kb in size and encodes a polypeptide of 310 amino acid residues with a molecular mass of 33 kD. AtFbr1 is expressed at high levels in the flower and root tissue and at a slightly lower level in leaf tissue, whereas it was nearly undetectable in siliques. Expression of AtFbr1 was compared with that of the FLP (fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…However, Kap121p mediates its import through a direct interaction with the N-terminal rg-NLS. This establishes Nop1p as the first member of a novel class of Kap121p cargoes and extends previous studies implicating the Nop1p GAR domain in nuclear localization (40,49). Interestingly, this novel Kap121p-recognized rg-NLS sequence is similar to the rg-NLS sequences of the Kap104p import cargoes Nab2p and Nab4p.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, Kap121p mediates its import through a direct interaction with the N-terminal rg-NLS. This establishes Nop1p as the first member of a novel class of Kap121p cargoes and extends previous studies implicating the Nop1p GAR domain in nuclear localization (40,49). Interestingly, this novel Kap121p-recognized rg-NLS sequence is similar to the rg-NLS sequences of the Kap104p import cargoes Nab2p and Nab4p.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, localization studies of Nop1p homologues identified the evolutionarily conserved N-terminal domain as possessing nuclear localization activity. In the case of human Nop1p (fibrillarin), the domain was required, but not sufficient, for nuclear import (49), whereas in Arabidopsis the GAR domain of AtFbr1 was both necessary and sufficient to target this protein to nucleoli (40). These data suggested that if Kap121p indeed mediates the import of Nop1p, it may do so through a kind of NLS that is different from those previously characterized.…”
Section: Resultsmentioning
confidence: 41%
“…5E; Lee et al, 2002). In contrast, GFP signals accumulated specifically in the nucleus when GFP was fused to the nuclear localization signal of the fibrillarin protein from Arabidopsis (Pih et al, 2000). In addition, GFP signals were found to accumulate in both the cytoplasm and the nucleus when Arabidopsis was transformed with the control vector without a specific targeting sequence, and no GFP signal was detected in wild-type, untransformed plants.…”
Section: Dg1 Encodes a Ppr Protein Targeted To The Chloroplastmentioning
confidence: 92%
“…DNA encoding the full-length LTD protein was amplified by PCR using prime LTDGFPF and prime LTDGFPR, and the PCR products were ligated into the GFP fusion vector pUC18-35s-sGFP with GFP as a reporter. The constructs for nuclear, chloroplast and mitochondria localization were constructed according to the previous methods 31,32,33 . The resulting fusion constructs and the control vector were introduced into wild-type Arabidopsis.…”
Section: Methodsmentioning
confidence: 99%
“…31). GFP fusion proteins with the targeting signals of fibrillarin 32 and FRO1 (ref. 33) of Arabidopsis were located specifically in the nucleus and mitochondria, respectively (Fig.…”
Section: Cellular Localization Of Ltdmentioning
confidence: 99%